Aplikasi E Counseling Siswa SMK TI Garuda Nusantara Cimahi - Dedy Apriadi; Raafi Meynda Putra (Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2023)
E-Counseling is one of the media that is devoted to accommodate problems in students with online media. With the application of online counseling, it is hoped that counseling guidance activities can run more effectively. Counseling activities by manual method using paper media are considered less effective. So it takes a long time and has a lot of risk of losing data. Loss of data and making reports still in the book is certainly a problem because finding data and making reports is also difficult because it takes a long time to collect data that will be used as reports. The web-based e-counseling system is a web system built using the Waterfall Software Development Life Cycle (SDLC) method which has 6 stages including Requirements Analysis, System Design, Program Code Writing, Program Testing and Program Implementation. Designing a solution in the form of a wireframe website for an e- counseling system, if it is finished then it goes to the Coding stage or builds a system using the PHP and MySQL programming languages.This application get the expected result. Its functions run well and are well received by users of SMK TI Garuda Nusantara Cimahi. The scenario used uses Blackbox